Influence of the Composition of the Mixture and the Type of Processed Fibers on the Quality Indicators of Fabrics - Patxullayev S.; Mengnarov Sh.S.; Ismoilov D.A. (International Journal on Orange Technologies, 2024)
This article presents the results of studies to determine the influence of the type of fibers and recycled fibrous waste on the quality indicators of fabric. For this purpose, in production conditions, a sliver with a linear density of 5000 tex was obtained on a JFA-226 carding machine, and in the laboratory of the Department of Spinning Technology, slivers were also obtained in three versions on an HSR-1000 brand draw machine. To obtain twill weave fabric on a Picanol loom, warp threads were mixed with yarn consisting of 100% cotton, and weft thread was mixed with yarn consisting of recycled fibers and the quality parameters of the fabric were examined.